The impact of population, affluence, technology, and urbanization on CO₂ emissions across income groups - Lars Sorge; Anne Neumann (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
This paper analyzes the impact of urbanization on CO2 emissions within the STIRPAT framework over the period 1971 to 2014 for a panel of 76 countries clustered into income groups. Using dynamic panel estimations techniques, the empirical results robustly show an inverted N-shaped relationship between urbanization and CO2 emissions in the long-term associated with the ecological modernization theory in particular for the lower- and middle-income panel: increasing levels of urbanization tend to reduce CO2 emissions in the long-term. The estimated turning point for the urbanization ratio after which CO2 emissions decline is almost identical and around 54% both for the lower- and middle-income panel. The long-term relationship for CO2 emissions and its relevant impact factors tends to be similar across groups. The impact of population determines CO2 emissions significantly only in the long-term within any panel. Different from previous studies, the results robustly indicate that GDP per capita does impact CO2 emissions greater than population in any panel. This suggests, that it is rather the growth in consumption than the number of people leading CO2 emissions to increase. Energy efficiency reductions most harmfully effect CO2 emissions within the high-income panel in the long- and short-run.
Keywords: Q5; Q43; R11; C23; 330; STIRPAT; carbon dioxide emissions; urbanization; ecological modernization; level of economic development; panel data data methods